How to engage with stakeholders through qualitative research - Lee, Mandy (Health Service Executive, 2015)
This article provides an overview of qualitative research, focusing on key methods and approaches that would be useful for conducting exploratory investigations into service delivery and organisation in health and social care. We start with a discussion of the rationale for conducting qualitative research in health and social care, and proceed to cover two data collection methods most used in qualitative studies: interviews and focus groups. In addition to providing practical tips on how to collect data using these two methods, the discussion will centre on the theoretical and practical considerations that need to be taken into account when choosing between qualitative methods and approaches for one’s research project. Several qualitative research studies in health and social care will be discussed as examples to illustrate how such approaches contribute to our understanding on issues relevant to health and social care professionals in both policy and practice.
How to Conduct Research for Service Improvement: A Guidebook for Health and Social Care Professionals. (2nd Edition)
Keywords: QUALITATIVE RESEARCH; stakeholder engagement